HUKUMAN CAMBUK BAGI PELAKU JARIMAH ZINA DALAM HUKUM PIDANA ISLAM ( Studi Putusan MAHKAMAH Syar’iyah Lhokseumawe Nomor 4/JN/2018/MS.Lsm ) - Zama, Aditya (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
Islamic criminal law considers that every perpetrator of adultery or a person who engages in sexual relations outside of marriage is punishable by punishment, whether the perpetrator is married or not, whether they are consensual or not, because Jarimah (criminal act) for adultery in Islamic law is categorized as Jarimah hudud. The formulation of the problem in this paper is as follows, how are the rules of caning for adultery perpetrators in Islamic criminal law, how is the application of sanctions / canings against the perpetrators of zina zina in Islamic criminal law, how are judges' legal considerations in the application of flogging law against adultery perpetrators based on the decision of the Lhokseumawe Syar'iyah Court. The type of research in this research is normative legal research with a normative juridical approach. Normative legal research is also called doctrinal legal research, where law is conceptualized as what is written in laws and regulations (law in books) and research on legal systematics can be carried out if there are certain statutory regulations or written law. The data collection technique in this research is library research, which is "research to get an overview or information about similar research and related to the problems being studied. The regulation of caning for adultery perpetrators in Islamic criminal law is being flogged a hundred times according to the word of Allahswt. Surat an-Nur paragraph 2, while Article 33 (1) of the Aceh Qanun Number 6 of 2014 concerning the Jinayat Law states that anyone who deliberately commits adultery, is threatened with 'uqubat hudud, 100 (one hundred) lashes. Aceh Qanun Number 6 of 2014 concerning the Law of Jinayat does not differentiate between adulterers muhshan and ghairu muhshan, which means that adulterers in Aceh, both married and unmarried, receive the same severe sentence of 100 (one hundred) lashes. The application of sanctions / caning punishments for adultery perpetrators in Islamic criminal law must be carried out and witnessed by a group of believers, meaning that it must be in an open place and can be seen by others. The objective is for learning and prevention, both for the perpetrator of the crime himself and for other people.